FATIGUE FAILURE ANALYSIS CC20143 LOCOMOTIVE AXLE - VALENTINO WILLYANTO (NIM : 131 04 038); Tim Pembimbing : Prof. Dr. Ir. Mardjono Siswosuwarno, STEVEN
CC20143 locomotive axle had sufferred a fatigue failure although it was designed for infinite life. Preliminary observation on the surface of the axle which interfere with the wheels show signs of wheel removal scratches and fretting marks. On the fracture surface, jog, beach marks, and final failure can be seen. These show that the axle fails because of fatigue. Analysis was performed by calculating the occurring load on fracture location using mechanics calculations, fatigue load calculation, and finite element modeling using Ansys 12.0. Finite element modeling is needed to calculate the occurring load on normal press fit condition, conical press fit condition, and without press fit. The load calculation result is below axle yield strength. Axle failure occurred due to impact load of wheel movement toward axle. Impact load occurs because of gap existence over fit looseness. The gap existed on the wheel and formed by bad wheel turning process.